Exit from an interval by a difference of two renewal processes - Kadankov, V. (Інститут математики НАН України, 2005)
Integral transforms of the joint distribution of the ﬁrst exit time from an interval,
the value of the overshoot through a boundary, and the value of a linear component
at the epoch of the exit are determined for the difference of two renewal processes.